Liderazgo ambidiestro y colaboración en red: estudio de caso de construcción de futuros organizacionales en el sector público uruguayo - Azevedo, Verónica (2025)
A case of social construction of the future in a Uruguayan public sector organization is analyzed. The original problem was the need for investments to expand energy infrastructure, with an impact on the satisfaction of demand for social and industrial purposes at a national level. To establish the baseline and measure progress, an organizational ambidexterity model was used. Prospective methodologies were applied to formulate the desired scenario and two hypotheses were proposed for its construction: 1) a particular leadership is required, 2) specific tools are needed to articulate collaboration between actors. Ambidextrous leadership and network collaboration models were developed and validated, which allowed for the improvement of key dimensions. The work contributed to understanding how foresight can be used in a company to sustainably improve its results and the role of leadership in the construction of the desired scenario.